Projetos experimentais para o ensino de microbiologia na educação básica e segurança no descarte de resíduos - Tatiana Augusta Araújo de Souza (2023)
Microbiology is the branch of biology that studies bacteria, fungi, protozoa, unicellular algae, viruses, viroids and prions. Basic knowledge about microorganisms is extremely important because it is directly linked to health and personal hygiene, as well as other important aspects related to the functioning of the environment, deserving a prominent role in science and biology teaching. It is common to observe in many basic education schools classes taught in an expositive and dialogic way without any application of investigative practice, which makes efficient and meaningful scientific learning difficult. It is important to apply practical classes in teaching-learning strategies, so that the world of microorganisms ceases to be abstract for students. The practical activities are effective in terms of teaching microbiology because they arouse the students' interest and curiosity, allowing them to correlate with issues of everyday life that involve health and well-being. The objective of the present work was the elaboration of a guide with experimental projects to demonstrate microorganisms or microbiological processes, destined to be used in the teaching of microbiology in basic education schools. The guide presents practices on microbial ubiquity, hand antisepsis – action of antiseptics, preparation of alternative culture media, investigation of microorganisms on objects and surfaces, decomposition systems, fermentation by yeast and milk fermentation, memory game viruses and viruses and targeted study on antibiotic resistance. All proposed practices guide the use of alternative materials and a disinfection protocol, aiming to reach the reality of schools that do not have laboratories. For the elaboration of the disinfection protocol, the effectiveness of sodium hypochlorite was tested against cultures of Escherichia coli, Bacillus cereus, Saccharomyces cerevisiae and microorganisms resulting from the practice of ubiquity. Petri dishes containing microorganism colonies were incubated for 24 hours in the presence of 2% sodium hypochlorite, the biological material was collected, washed and plated again. Hypochlorite showed 100% efficiency in the disinfection of Petri dishes containing the tested colonies. The protocol proved to be efficient, allowing disinfection for safe disposal of contaminated materials resulting from the experiments, in schools that do not have autoclave devices for correct sterilization of products from practical classes.